CIRC for Improving Reading Comprehension Skill in 4th Grade Elementary School Students - Budiarti, Tisna; Sa’ud, Udin Syaefudin; Cahyani, Isah (International Conference on Elementary Education, 2020)
This study aims to determine whether the learning design using the CIRC type in cooperative learning model can improve reading comprehension skills in fourth grade students of elementary schools. This study focused on the steps of the CIRC type of this model emphasizes student’s teamwork in finding the main ideas of some texts. The learning process is centered on student and their group activities. Meanwhile, teacher provides some guidance for each group. This study used a quasi-experimental method and used a nonequivalent control group design. This research was conducted in 4th grade elementary students in one of school in Lampung Tengah Regency (22 participants). The result shows that the design of CIRC type in cooperative learning models can improve the reading ability of 4th grade elementary students’ understanding